Heterogeneity in the osteotrophic response to exercise during different stages of puberty - Saxon, L.; Bass, S.; Daly, R. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
Very little is known about the surface specific effects of exercise on cortical bone in humans. It has been hypothesised that exercise increases bone accrual on the periosteal surface during pre-menarcheal years and on the endocortical surface after menarche.1 The aim of this study was to determine the effect of exercise on bone mass (BMC), bone geometry, and volumetric bone density (vBMD) during different stages of growth. These traits were compared in the playing and non-playing humerii of 6 pre-menarcheal, and 13 post- menarcheal (1.8 ± 0.2 yrs) female tennis players. Bone geometry and BMC of humeral mid-third was determined using magnetic resonance imaging (MRI) and DEXA respectively. The pre- and post- menarcheal players were aged 12.1 ± 0.7 and 14.2 ± 0.5 yrs, had been training for 5.6 ± 0.7 and 6.9 ± 0.3 yrs, and were currently training 8.9 ± 1.9 and 10.9 ± 1.4 hr • wk-1 respectively. There was no difference between groups for years training prior to menarche (~5.3 yrs). The table below (mean ± SE) shows the side-to-side differences (except medullary volume) ranged 8 to 32% in the pre- and 6 to 14% in the post- menarcheal players (p<0.05-0.001). The side-to-side differences in BMC and vBMD were greater in the pre- compared to the post- menarcheal players (p<0.05). The osteotrophic response to training occurred on the periosteal surface (8.2%) in the pre-menarcheal players and periosteal (6.1%) and endocortical surfaces (2.4%) in the post-menarcheal players. In the post-menarcheal players the side-to-side difference in cortical area was greater distally than proximally (21.9 vs 13.6 mm2, p<0.05) whereas there was no difference in the pre-menarcheal players. In the medullary cavity the side-to-side difference in the post-menarcheal players was due to contraction distally and expansion proximally (-4.2 vs 3.5 mm2 p<0.001). In the pre-menarcheal players there was expansion proximally but no difference distally (7.6 vs 0.0mm2 p<0.01). In conclusion, the greatest osteotrophic benefits from exercise appear to be achieved in the pre-menarcheal years. Further, the proposed model for the surface specific osteotrophic response to exercise is more complex than previously hypothesised.